Electrocardiographic changes induced by temperature variations in newly hatched Aperema (Rhinoclemmys punctularia, Daudin, 1801) - Cardoso, Deise de Lima; Braga, Brenda Stefany dos Santos; de Araújo, Daniella Bastos; da Paz, Clarissa Araújo; Eiró-Quirino, Luciana; Reis, Thaysa de Sousa; de Souza, Luana Vasconcelos; Ferreira, Rayllan da Cunha; Barbosa, Gabriela Brito; de Souza, Raíssa Vieira; Deiga, Yris da Silva; Hamoy, Maria Klara Otake; et al. (Frontiers in Veterinary Science, 2025)
IntroductionAperema (Rhinoclemmys punctularia) is a South American semi-aquatic freshwater turtle characterized by a highly curved, dark brown to black carapace and is distributed across Central and South America. Climate change affects freshwater turtles in a number of ways, including temperature, hatchling sex, and survival.MethodsTherefore, we analyzed temperature variations in these turtles through electrocardiographic recordings, since studies on temperature variations in R. punctularia are limited.Results and discussionElectrocardiography (ECG) is a highly relevant diagnostic tool as it allows for precise assessments of cardiac events and is non-invasive. The development of non-invasive ECG measurement methods is crucial for evaluating and maintaining the health of chelonian individuals during veterinary treatment or experimental procedure. Our findings revealed that heart rate is temperature-dependent, showing that lower environmental temperatures result in decreased heart rates. Therefore, we demonstrated through the electrocardiographic patterns observed during the experiment that a reduction in the ambient temperature to which Rhinoclemmys punctularia are exposed can modulate the conductivity and automaticity of cardiac cells, subsequently leading to a decrease in heart rate.